Teacher`s role in distance learning - Іваненко, Л. О. (Scientific notes of the pedagogical department, 2017)
The article describes the features of the use of distance learning as a new form of education, which naturally absorbs the computer and Internet technologies. Showing the distance learning differs from traditional. It was revealed that distance learning can be regarded as an independent form of education, because it has significant differences, which can not be implemented in the traditional way, but still not be able to completely replace the traditional forms of learning. It has been shown that the development of distance learning changes the ways, methods and means of the educational process in higher education contributes to the intensification of the educational process, improves information resource provision is a prerequisite for the development of qualitatively new methods of teaching students in higher educational institutions. Shown as qualitatively changing role of the teacher: knowledge of the translator, he turns into a successful organizer of the learning process and the creator of an effective learning environment. Teacher in distance learning system provides training and methodological support and solve organizational issues related to the control of the performance and quality of Learning students in the learning process. The main function of the teacher in distance education.